PP77 General Practitioners (GPs), patients and cancer screening. (2nd September 2014) - Green, T; Atkin, K; Macleod, U
Abstract : Background: In the UK, diagnostic delay is deemed to account for an estimated 5–10, 000 extra cancer deaths each year. Primary care has been identified as an area where explanation for this might be found and is the focus of considerable research and policy activity. However, there is limited work that investigates GPs' understanding of awareness and early detection in relation to general practice. The overall purpose of our study was to understand cancer diagnosis from the perspective of GPs, and to develop a framework for conceptualising the potential of the GP role to improve cancer recognition and referral. One area of focus was to explore GPs' perceptions of asymptomatic cancer screening programmes. Specifically we aimed to identify GPs' understanding of their role with respect to cancer awareness, screening and early detection, to examine their attitudes to screening, and elicit their views on the role of primary care in supporting screening coverage. Methods: Individual face-to-face interviews were conducted with 55 GPs, four of whom were GP cancer leads. We also carried out 18 second interviews over the telephone. Cancer leads were not re-interviewed. Participating practices were in the North and North East of England (n.45) and Greater London (n.10). Purposeful sampling ensured demographic diversity of practices. GP informants were equally diverse regarding gender, ethnicity, age, years in practice and position held. All interviews were recorded and transcribed verbatim. Repeated reading of GPs' narratives engendered thematic analysis across the interview material, this included GPs' understandings of developments of screening programmes; reasons for lack of uptake in some patient cohorts; and GPs' perceptions of their role in improving screening uptake in hard-to-reach patient groups. Results: Primary care was perceived as the most appropriate host for screening programmes. Enhancing the uptake of cervical screening was perceived as more manageable because of its embeddedness within primary care. Breast and bowel screening created several challenges, for example, there was GP consensus on the issue of patients' informed choice, but recent breast screening debates created difficulties during GP/patient interactions. Issues raised by GPs' endorsement of bowel cancer screening ranged from patients' reluctance to participate to communicating the implications of positive test results to patients. Conclusion: Input from primary care would contribute to the development of screening programmes. GPs' understandings of their practice populations would assist in targeting underserved areas that fall below the national average for asymptomatic screening.